Wurde Tyras in das Römische Reich inkorporiert? Ein Beitrag zur Geschichte der Römischen Anwesenheit an der Nördlichen Schwarzmeerküste - Królczyk, Krzysztof (Studia Europaea Gnesnensia, 2017)
The following text has been devoted to the problem of incorporation of the Greek colony of Tyras, located not far away from the mouth of the river Tyras (Dniester) into the Pontus Euxinus (Black Sea), to the Roman Empire. Some scholars – among them Theodor Mommsen – were convinced that it happened in the middle of the 1. century AD or little later. There are, however, some historians who think that Tyras remained independent until its end in the late antiquity. Upon the analysis of the extant epigraphic sources, the author of the following article puts a hypothesis that Tyras was actually incorporated to the Roman province by the end of the 2. century AD. In his opinion it was the emperor Septimius Severus (ruled 193-211) who decided to enlarge the territory of the Empire in this part of the ancient oikumene. The incorporation of Tyras into the Roman Empire can bee seen as a part of the policy of the propagatio Imperii (the enlargement of the Empire) which was consistently carried out by Septimius Severus from the very beginning of his reign.